ChemInform Abstract: Alkyne Difunctionalization by Dual Gold/Photoredox Catalysis. Issue 36 (August 2016) - Tlahuext‐Aca, Adrian; Hopkinson, Matthew N.; Garza‐Sanchez, R. Aleyda; Glorius, Frank
Abstract: A selective tandem nucleophilic addition/cross‐coupling reaction of alkynes using visible‐light‐promoted dual gold/photoredox catalysis is developed.